Tumor−associated macrophage polarization in the inflammatory tumor microenvironment - Zou, Zijuan; Lin, Hongfen; Li, Mengsen; Lin, Bo (Frontiers in Oncology, 2023)
The chronic inflammation of tumor continues to recruit TAMs (tumor‑associated macrophages) to the TME (tumor microenvironment) and promote polarization. Pro-inflammatory signals polarize macrophages to the M1 phenotype to enhance inflammation against pathogens. Tumor inflammatory development changes the pro-inflammatory response to an anti-inflammatory response, resulting in the alteration of macrophages from M1 to M2 to promote tumor progression. Additionally, hypoxia activates HIF (hypoxia-inducible factors) in the TME, which reprograms macrophages to the M2 phenotype to support tumor development. Here, we discuss the factors that drive phenotypic changes in TAMs in the inflammatory TME, which will help in the development of cancer immunotherapy of macrophages. Keywords: tumor-associated macrophages; polarization; inflammatory; tumor microenvironment; cancer immunotherapy of macrophages.